Marsela in motion: The Babar islands in eastern Indonesia and the outer world. Issue 138 (4th May 2019) - van Dijk, Toos
ABSTRACT: The small island Marsela, one of the Babar islands of Maluku province in eastern Indonesia, has long been of little interest to central authorities given its location at the edge of their spheres of influence and its presumed economic insignificance. Even after lasting contact with western civilisation was established in the first decades of the 20th century, it remained a rather forgotten island. This article aims to show that, despite its remoteness, Marsela's relationship with the outer world is considered vital by its population. An insightful way to look at this relationship is to examine trade. Hence it discusses the bartering systems in which the Marsela have been engaged for centuries to obtain (luxury) consumer goods from neighbouring islands, and from Banda, India, and the Netherlands. Its message is that a focus on the outside is embedded in Marsela culture. It is given concrete expression in rituals and myths and sets society in motion. Recent plans to exploit an enormous gas-field off the coast of Marsela add an unforeseen factor to this picture.